Reappraising medfly longevity: A quantile regression survival analysis - Roger Koenker; Olga Geling (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Chaudhuri, Doksum and Samarov (1997) have recently stressed the usefulness of the quantile regression formulation for survival analysis and for transformation models, more generally. In this paper, we explore the use of quantile regression in survival analysis by reanalysing a large experimental study by Carey, Liedo, Orozco, and Vaupel (1992), that monitored age-specific mortality in a population of roughly 1.2 million Mediterranean fruit flies (Ceratitis Capitata). The quantile regression approach appears useful in refining several of the conclusions drawn from this study including the apparent decline in mortality rates at advanced ages, and the gender cross-over effect in survival functions for medflies.
urn:nbn:de:kobv:11-10046423
Keywords: 330